Estratégias pedagógicas no ensino da clínica ampliada na atenção primária à saude: percepções e vivências dos alunos de graduação médica - Martins, Mariana Pavan [UNESP] (2015)
The Medical School of Botucatu (FMB) - UNESP, since 2002, has participated in programs offered by the Ministries of Health and Education which aim to guide the formation of professionals in the health area. In 2003, FMB-UNESP implemented the program Interaction University-Service-Community - IUSC, in response to the Program of Curricular Changes (PROMED), allowing the broadening of experiences for the undergraduate students in the community. The discipline IUSC uses the experiences of students in the Primary Attention Health Service (PAHS) as teaching-learning strategy and is developed with students from the three first years of the medical school and first and second years of the nursing course (in the two first years all the activities are developed as inter professional education practice). The aim of this study was to evaluate and characterize three educational strategies used in the discipline IUSC III related to its theoretical and educational basis. Such strategies (supervised assistance for patients with frequent follow up, guided by expanded scripted anamnesis) aim the broadening of clinics and are oriented by the humanization and integrality of care. The participants were under graduate students of the third and sixth years of medical school. A questionnaire was used with the students of the third year (78 students, corresponding to 88.6% of the total group) and semi structured interviews were used with the students of the sixth year (six students). The quantitative data were analyzed by descriptive statistics and the qualitative data by the Thematic Content Analysis. The students evaluated that such strategies contributed to the acquisition and/or the development of clinical competences being several of them related to the comprehension of health and the problems in a broadening perspective and the development of skills related to communication (including the relation student-patient and a qualified hearing). From the ...